Spatio-Temporal Analysis of Dengue Cases in Kuningan District Since 2008-2017 - M. Ezza Azmi Fuadiyah; Andri Ruliansyah (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
Dengue has spread to over 400 of Indonesia’s 497 districts, including West Java Province in which 26 of its districts have been declared as hyper-endemic. A study was conducted to describe the spread of dengue incidences and its cluster during 2008-2017 in Kuningan District. The district is located in an important route, in migration and in the economic field, connecting the northern part of West Java to the southern part. A spatio-temporal analysis based on monthly dengue incidences from the local District Health Office was performed using SaTScan™. This study revealed there were Statistically significant high-risk dengue clusters with various RR in half of the subdistricts in Kuningan in the ten-year periods of 2008-2017 and a retrospective space-time analysis detected 17 significant clusters (P<0.001). Subdistrict Kuningan is detected as a high-risk area every year except for 2008, whereas Jalaksana emerged as a high-risk cluster in six of ten-year periods. We conclude that there was a dynamic spread of dengue cases initiated from the north part of Kuningan District to western areas. This study results do not properly predict RR due to a lack of information on some significant factors, such as vector density and related environmental and socioeconomic parameters. However, this study has provided a perspective on dengue incidence that can be used by local health managers and disease surveillance personnel to monitor prospective outbreaks and make decisions about how to implement an effective response.